Implikasi dan Implementasi Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 Terhadap Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja (Omnimbus Law) - Wardiyan, Riyan Agung (SIYASI: Jurnal Trias Politica, 2024)
The Constitutional Court Decision Number 91/PUU-XVIII/2020 regarding Law Number 11 of 2020 on Job Creation has created legal uncertainty due to ambiguities in its ruling. The decision declared the Job Creation Law conditionally unconstitutional due to formal defects in its formation, yet simultaneously stated it remains valid until revisions are completed within 2 years. This study aims to analyze the implications and implementation of this decision on legal certainty in Indonesia. The research employed a normative juridical approach by examining decision documents, legislation, and literature related to formal judicial review. The findings reveal contradictions between point 3 of the ruling, which states the law has no binding legal force, and point 4, which declares the law remains valid. The implications create problems regarding the validity and efficacy of the Job Creation Law, failing to meet juridical, philosophical, and sociological aspects as stipulated in Law Number 12 of 2011. Post-decision implementation has generated ambiguity concerning the boundaries of strategic policies with broad impacts, and confusion in regulatory hierarchy as the omnibus law method regulating 79 laws is incompatible with the Civil Law system adopted by Indonesia. The study concludes that the Job Creation Law experiences a legal vacuum as it remains valid but cannot be implemented, necessitating reevaluation of the Constitutional Court's decision to ensure legal certainty.